New project on hybrid renewable energy generation technology to Sri Lanka - Ratneswaran, K.; Amalendran, J.; Kokulasingam, V.; Alex Angelito, R.; Wickramasinghe, A.; Fernando, S.; Vigneswaran, P.; Atputharajah, A.; Mithulananthan, N. (My University, 2010)
Recent development in Sri Lanka will boost the electricity demand in near future. Extending national grid, especially for some islands, will cost more than installing renewable energy generation technologies. Justification studies confirmed that, for some islands closer to the northern part of Sri Lanka it is more cost effective to electrify with renewable sources. This paper discusses a new hybrid generation option for Eluvaithivu, an island located close to Jaffna, Sri Lanka. Eluvaithivu is a small island covering an area of 1.7 km2 with 130 houses. Seventy houses are supplied electricity by a 28 kVA diesel generator owned by the Ceylon Electricity Board and operated (CEB) from 4.30 am to 6.30 am and 6.00 pm to 10.30 pm. The average monthly consumption is 3,100 kWh. Cost of electricity generation is about 60 Rs/kWh while the average tariff is about 5Rs/kWh. This financial loss prevents the complete electrification of the island and round the clock supply to the island. Eluvaithivu is well exposed to both monsoons. According to a study done by National Renewable Energy Laboratory (NREL) study, the annual average wind speed is approximately 6.5 m/s. The first phase feasibility study proposes wind-diesel hybrid system as the most cost effective generation technology for this island. This will minimize the financial loss to the CEB by about 60% in supplying the electricity to this island while providing electricity round the clock. Currently, research studies are carried out to check the time domain plant operations with the recent hybrid control techniques. This will bring a solid hybrid system with optimized operational strategy between generators to effectively and efficiently electrify the island.